Insight into Nephrocan Function in Mouse Endoderm Patterning - Addeo, Martina; Buonaiuto, Silvia; Guerriero, Ilaria; Amendola, Elena; Visconte, Feliciano; Marino, Antonio; De Angelis, Maria Teresa; Russo, Filomena; Roberto, Luca; Marotta, Pina; Russo, Nicola Antonino; Iervolino, Anna; et al. (International journal of molecular sciences, 2019)
Endoderm-derived organs as liver and pancreas are potential targets for regenerative therapies, and thus, there is great interest in understanding the pathways that regulate the induction and specification of this germ layer. Currently, the knowledge of molecular mechanisms that guide the in vivo endoderm specification is restricted by the lack of early endoderm specific markers. Nephrocan (Nepn) is a gene whose expression characterizes the early stages of murine endoderm specification (E7.5–11.5) and encodes a secreted N-glycosylated protein. In the present study, we report the identification of a new transcript variant that is generated through alternative splicing. The new variant was found to have differential and tissue specific expression in the adult mouse. In order to better understand Nepn role during endoderm specification, we generated Nepn knock-out (KO) mice. Nepn−/− mice were born at Mendelian ratios and displayed no evident phenotype compared to WT mice. In addition, we produced nullizygous mouse embryonic stem cell (mESC) line lacking Nepn by applying (CRISPR)/CRISPR-associated systems 9 (Cas9) and employed a differentiation protocol toward endoderm lineage. Our in vitro results revealed that Nepn loss affects the endoderm differentiation impairing the expression of posterior foregut-associated markers.